2023
DOI: 10.3390/nu15163615
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk and Sarcopenia Features in Patients with Crohn’s Disease: Relation to Body Composition, Physical Performance, Nutritional Questionnaires and Biomarkers

Konstantinos Papadimitriou,
Paraskevi Detopoulou,
Konstantinos Soufleris
et al.

Abstract: Patients with Crohn’s disease (CD) face malnutrition risk, which, combined with inflammation, can lead to sarcopenia, associated with a worse prognosis. The purpose of the present study was to assess malnutrition and sarcopenia in patients with CD. Fifty-three patients (26 women) participated (38.1 ± 10.9 years, 79% in remission). Body composition, physical performance, nutritional questionnaires, and biomarkers were performed. Malnutrition was screened with the Mini Nutritional Assessment (MNA) and the Malnut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…While numerous studies have documented the decline in mental health among young individuals linked with lockdown periods, there is an absence of research in Greece concerning this specific age group [15]. As a result, the objective of this repeated cross-sectional pilot study is to investigate the influence of engaging in physical activity (PA) during the COVID-19 pandemic on the mental well-being of young adults (aged [18][19][20][21][22][23][24][25][26] in Greece. The study aims to assess alterations in PA levels and overall well-being, as indicated by anxiety and depression levels, since the commencement of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have documented the decline in mental health among young individuals linked with lockdown periods, there is an absence of research in Greece concerning this specific age group [15]. As a result, the objective of this repeated cross-sectional pilot study is to investigate the influence of engaging in physical activity (PA) during the COVID-19 pandemic on the mental well-being of young adults (aged [18][19][20][21][22][23][24][25][26] in Greece. The study aims to assess alterations in PA levels and overall well-being, as indicated by anxiety and depression levels, since the commencement of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Serum albumin, the main component of the GNRI, is closely associated with hs-CRP levels in patients with inflammatory diseases. For instance, patients with higher albumin tend to have higher triceps skinfold measurements reflecting upper arm muscle circumference and lower hs-CRP levels in those with Crohn’s disease ( 54 ). Moreover, malnutrition is known to weaken immune function owing to the loss of body proteins and energy restriction ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric variables were taken by trained regular personnel of the European Leagues, certified by ISAK, the International Society for the Advancement of Kinanthropometry, with a technical measurement error of 0.04% for basic measurements and of 2.12% for skinfolds, following the international standards recommended by the ISAK and by Papadimitriou et al [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The participants, during the measurement, remained relaxed in the supine position and with an empty stomach. The female athletes were in the mid-period of menstruation without any problems with menstruation [ 33 ]. Height was measured in centimeters using a wall-mounted stadiometer (Seca 214, SECA Deutschland, Hamburg, Germany), and weight was measured in kilograms with a high-precision scale (Tanita BC-418, Tanita, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation